IMPLEMENTATION OF THE MOORA METHOD IN DETERMINING CANDIDATES FOR VILLAGE HEAD - Fricles Ariwisanto Sianturi; Paska Marto Hasugian; Widia Putri; Ira Mayang Sari (Sean Institute, 2022)
One of the community democratization parties is the election of the village head, the election of the village head is carried out at the village level directly to determine the village leader or village head. Decision support system is an interactive alternative system that can assist in decision making through the use of data and decision models to solve semi-structured and unstructured problems. This system was built by applying the MOORA (Multi-Objective Optimization on the basis of Ratio Analysis) method where the basic concept of the MOORA method is to find the weighted sum of the performance ratings for each alternative on all attributes. In the calculation of the MOORA method, only the one that produces the largest value will be selected as the best alternative. Calculations will be in accordance with this method if the selected alternative meets the predetermined criteria. By using a decision support system for the selection of village head candidates using the Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) method, it helps community members to find out the ranking of village head candidates from the results of the weighted criteria that have been determined, thus providing additional information when making decisions. determine choices in the democratic party of the citizens of the village of Sitnggaling.